2002
DOI: 10.1109/20.996221
|View full text |Cite
|
Sign up to set email alerts
|

A new neural-network-based scalar hysteresis model

Abstract: A neural network (NN)-based model of scalar hysteresis characteristics has been developed for modeling the behavior of magnetic materials. The virgin curve and a set of the first-order reversal branches can be stored preliminary in a system of three NNs. Different properties of magnetic materials can be simulated by a simple if-then type knowledge-based algorithm. Hysteresis characteristics of different materials predicted by the introduced model are compared with the results of the classical Preisach simulati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
30
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(30 citation statements)
references
References 6 publications
0
30
0
Order By: Relevance
“…Due to its ability of universal function approximation, NN has been successfully used to design controllers for several kinds of unknown nonlinearities. However, few researches have been carried out by using NN to tackle hysteresis [21][22][23]. In [21,22], a NN model is used to describe the hysteresis behavior in different frequencies with the knowledge of some properties of magnetic materials, such as loss separation property to allow the separate treatment of quasi-static and dynamic hysteresis effects.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to its ability of universal function approximation, NN has been successfully used to design controllers for several kinds of unknown nonlinearities. However, few researches have been carried out by using NN to tackle hysteresis [21][22][23]. In [21,22], a NN model is used to describe the hysteresis behavior in different frequencies with the knowledge of some properties of magnetic materials, such as loss separation property to allow the separate treatment of quasi-static and dynamic hysteresis effects.…”
Section: Introductionmentioning
confidence: 99%
“…However, few researches have been carried out by using NN to tackle hysteresis [21][22][23]. In [21,22], a NN model is used to describe the hysteresis behavior in different frequencies with the knowledge of some properties of magnetic materials, such as loss separation property to allow the separate treatment of quasi-static and dynamic hysteresis effects. In [23], a modified Luenberger observer and a NN are used to identify a general model of hysteresis.…”
Section: Introductionmentioning
confidence: 99%
“…Accurate Identification of Hysteresis non linearity is a crucial task for many applications such as hysteresis nonlinearity control [1], control of Shape Memory Alloy (SMA) actuators [2][3] and Piezo actuators [4][5][6], Performance Evaluation of electromagnetic devices [7].…”
Section: Introductionmentioning
confidence: 99%
“…The original vector model introduced in [53] was subsequently generalized by defining a new type of projection for the applied field vector on each direction corresponding with one scalar model [56]. Models based on neural networks have also been introduced more recently (see for example [57]). A very comprehensive review of past and present modeling techniques may be found in [58].…”
Section: G Materials Modelingmentioning
confidence: 99%